An Overview of Different Techniques for Improving the Treatment of Pulmonary Hypertension Secondary in Systemic Sclerosis Patients - Barbara Ruaro; Francesco Salton; Elisa Baratella; Paola Confalonieri; Pietro Geri; Riccardo Pozzan; Chiara Torregiani; Roberta Bulla; Marco Confalonieri; Marco Matucci-Cerinic; Michael Hughes (Diagnostics, 2022)
In systemic sclerosis (SSc) mortality is mainly linked to lung involvement which is characterized by interstitial lung disease (ILD) and pulmonary hypertension (PH). In SSc, PH may be due to different etiologies, including ILD, chronic thromboembolic disease, pulmonary veno-occlusive disease, and pulmonary arterial hypertension (PAH). The main tool to screen PAH is transthoracic echocardiography (TTE), which has a sensitivity of 90%, even if definitive diagnosis should be confirmed by right heart catheterization (RHC). The radiological evaluation (i.e., HRTC) plays an important role in defining the possible causes and in monitoring the evolution of lung damage. For PAH, identifying individuals who have borderline elevation of pulmonary arterial pressure needs to be appropriately managed and followed. In the past few years, the strategy for the management of PAH has significantly evolved and new trials are underway to test other therapies. This review provides an overview of the tools to evaluate PAH in SSc patients and on treatment options for these patients.